USE OF INFORMATION TECHNOLOGIES IN SELF-STUDY WHEN LEARNING FOREIGN LANGUAGES BY STUDENTS - Farxodova, Gullola (Журнал иностранных языков и лингвистики, 2021)
The fundamental requirement of society for modern education is the formation of a personality that would be able to independently creatively solve scientific, industrial, social problems, think critically, develop and defend your point of view, your beliefs, systematically and continuously develop and update their knowledge by self-study, improve skills, creatively apply them in reality. One of the most affordable and proven ways to improve efficiency of knowledge is the appropriate organization of independent educational work. It occupies an exceptional place at the present stage, because the student acquires knowledge only in the process of personal self-study activities. The article deals with the use of information communication technologies in earning the foreign language. The author emphasizes the effectiveness of using ICT in learners’ self-study